R-loop-dependent rolling-circle replication and a new model for DNA concatemer resolution by mitochondrial plasmid mp1. - Backert, Steffen (EMBO Journal, 2002)
The mitochondrial (mt) plasmid mp1 of Chenopodium album replicates by a rolling-circle (RC) mechanism initiated at two double-stranded replication origins (dso1 and dso2). Two-dimensional gel electrophoresis and electron microscopy of early mp1 replication intermediates revealed novel spots. Ribonucleotide (R)-loops were identified at dso1, which function as a precursor for the RCs in vivo and in vitro. Bacteriophage T4-like networks of highly branched mp1 concatemers with up to 20 monomer units were mapped and shown to be mainly formed by replicating, invading, recombining and resolving molecules. A new model is proposed in which concatemers were separated into single units by a "snap-back" mechanism and homologous recombination. dso1 is a recombination hotspot, with sequence homology to bacterial Xer recombination cores. mp1 is a unique eukaryotic plasmid that expresses features of phages like T4 and could serve as a model system for replication and maintenance of DNA concatemers.